New insights in atmospheric acid-catalyzed gas phase hydrolysis of formaldehyde: a theoretical study. Issue 42 (8th April 2015) - Liu, Fang-Yu; Tan, Xing-Feng; Long, Zheng-Wen; Long, Bo; Zhang, Wei-Jun
Abstract : A two-step mechanism of the gas phase hydrolysis of formaldehyde catalyzed by nitric acid. Abstract : The gas phase hydrolysis of HCHO catalyzed via nitric acid and acetic acid, the typical atmospheric acids has been theoretically investigated using M06-2X, CCSD(T), and CCSD(T)-F12A theoretical methods using the 6-311++G(d, p), aug-cc-pVTZ, and VTZ-F12 basis sets and utilizing transition state theory. Our studies predict that when the HNO3 or CH3 COOH and HCHO⋯H2 O act as reactants, the reactions occur in one step, whereas the reactions of HNO3 ⋯H2 O or CH3 COOH⋯H2 O with HCHO proceed via a two-step mechanism. Our results also show that the free energy barrier of the gas phase hydrolysis of HCHO assisted by HNO3 or CH3 COOH is reduced to 13.95 or 14.27 kcal mol −1 relative to the respective pre-reactive complex from 40.23 kcal mol −1 in the naked HCHO + H2 O reaction. The calculated kinetic data suggests that the HCHO + HNO3 ⋯H2 O entrance channel with a two-step mechanism is 1.84–2.76 times faster than HNO3 + HCHO⋯H2 O with a one-step mechanism, whereas the HCHO⋯H2 O + CH3 COOH entrance path is significantly more favorable than that of HCHO + CH3 COOH⋯H2 O, in the temperature range of 200–300 K. The reaction rates of the gas phase hydrolysis of HCHO catalyzed by HNO3 or CH3 COOH are much slower than that of the gas phase reaction of HCHO with an OH radical, which demonstrates that the contributions of both catalytic reactions are of minor importance for the sink of HCHO in gas-phase atmospheric chemistry. However, the new findings in this investigation are not only of great necessity and importance for elucidating the gas phase hydrolysis of formaldehyde, but are also of great interest for understanding the importance of other carbonyl compounds in the atmosphere.